Study on the Effects of the COVID-19 Pandemic on Romanian Businesses - Cristina Elena BIGIOI; Andreea Mirabela BUDULAN; Adrian Doru BIGIOI (Communications of International Proceedings, 2021)
The COVID-19 Pandemic caused significant disruptions to the economy and people's lives. The last two years have been a difficult period for many companies, as social isolation measures have influenced their economic position. Also, staying in the market has been a real challenge for most of them. This paper presents the results of a research on the effects of the COVID-19 Pandemic on Romanian companies. The research focused on such aspects as personnel changes, sales evolution and on the ways to manage the impact of the Pandemic on the activity they normally perform. The study shows that the companies registered decreases in turnover in 2020 compared to the year before the pandemic, but there were also companies with increases in turnover. There is no direct relationship between the field of activity and the evolution of turnover. The productivity of employees who have worked online does not affect turnover. Identifying new customers and reducing costs are considered to keep the company on the market.
Keywords: COVID-19; Romanian companies; entrepreneurs; economic impact